(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we will study on training and development programmes of employees. The response of most frequently thought and important issue on why firms require policies and practices because they deal with the major resource which is termed as human resource. Hence, it becomes inevitable for any firm to develop, communicate and enforce set of policies and practices that are acceptable to the firm. It then depends upon firm as for how they perceive these practices, as the role of practices should not be limited to draw the boundaries but to address and recognize people’s needs. Now once firms are actually exposed to the matter that performance improvement is all about establishing the system of developing and meeting the employee’s expectations. The present research also provides a thorough analysis of the influence or correlation between these hrm activities with employee efficiency organizational productivity.